2019
DOI: 10.3892/mmr.2019.10067
|View full text |Cite
|
Sign up to set email alerts
|

An lncRNA‑miRNA‑mRNA ceRNA network for adipocyte differentiation from human adipose‑derived stem cells

Abstract: Human adipose tissue-derived stromal stem cells (HASCs) represent a promising regenerative resource for breast reconstruction and augmentation. However, the mechanisms involved in inducing its adipogenic differentiation remain to be fully elucidated. The present study aimed to comprehensively investigate the expression changes in mRNAs, microRNAs (miRNAs) and long non-coding (lnc)RNAs during the adipogenic differentiation of HASCs, and screen crucial lncRNA-miRNA-mRNA interaction axes using microarray datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The alterations of compartment types (from A to B, or from B to A) mean that changes of chromatin state (from an open active state to a closed inactive state, vice versa) directly affect the inhibition or activation of gene expression. Here, the KEGG pathways showed that the genes within A to B compartment switching regions were clustered to neuroactive ligand-receptor interaction, which has been proven to exert a role in adipocyte differentiation in human adipose-derived stem cells ( Guo and Cao, 2019 ) and bovine muscle development ( Cassar-Malek et al, 2007 ). Furthermore, the genes within the B to A compartment switching regions were significantly involved in the calcium signaling pathway, a highly versatile intracellular signal being capable of regulating many different processes ( Berridge, 2012 ), as well as the TGF-β signaling pathway, which could multifunctionally regulate many cellular processes including cell growth, cell differentiation, apoptosis, morphogenesis, immune regulation, wound healing, inflammation, and cancer in both adult organisms and developing embryos ( Morikawa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The alterations of compartment types (from A to B, or from B to A) mean that changes of chromatin state (from an open active state to a closed inactive state, vice versa) directly affect the inhibition or activation of gene expression. Here, the KEGG pathways showed that the genes within A to B compartment switching regions were clustered to neuroactive ligand-receptor interaction, which has been proven to exert a role in adipocyte differentiation in human adipose-derived stem cells ( Guo and Cao, 2019 ) and bovine muscle development ( Cassar-Malek et al, 2007 ). Furthermore, the genes within the B to A compartment switching regions were significantly involved in the calcium signaling pathway, a highly versatile intracellular signal being capable of regulating many different processes ( Berridge, 2012 ), as well as the TGF-β signaling pathway, which could multifunctionally regulate many cellular processes including cell growth, cell differentiation, apoptosis, morphogenesis, immune regulation, wound healing, inflammation, and cancer in both adult organisms and developing embryos ( Morikawa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe the sequencing or microarray technology may be more mature recently and thus the results may be more believable. This was also indirectly reflected by the less overlapped genes if the other datasets were used (only two comparing with ; Guo & Cao, 2019) and thus, we renounced the use of multiple datasets and only the newly one. Moreover, this work investigated lncRNA co-expression and ceRNA mechanisms, which required the lncRNA and mRNA should be simultaneously analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that lncRNAs can act as ceRNAs to indirectly regulate mRNAs by competitively binding miRNAs [10,15,44]. lncRNA-associated ceRNA networks in human adipocyte differentiation have been constructed [45,46], and lncRNAs regulating adipocyte differentiation as ceRNA in human [13], bovine [15], and mouse [47] have been identified. Nevertheless, the specific lncRNA-associated ceRNA network involved in the differentiation of chicken preadipocytes is yet largely unknown.…”
Section: Discussionmentioning
confidence: 99%